The Factor of Influence on Purchasing Decision on Iphone Mobile Cases of Tokopedia - Widikasari, Siti Fauniza; Setiawan, Aries; Mahmud, Mahmud; Aqmala , Diana (Jurnal Manajemen dan Inovasi (MANOVA), 2024)
The reason of the study was to determine the impact of product quality, price, brand image and online customer reviews on purchasing decisions for Iphone mobile caseing on Tokopedia with a case study of Dian Nuswantoro University understudies. The research method utilized was quantitative method, with a test of 100 Dian Nuswantoro University students. Tools to analyze the information has been collected, analysts use the Smart PLS program version 3.0. The results appeared that item quality has an impact on purchasing decisions, cost has no impact on purchasing decisions, brand image has an impact on purchasing decisions, and online customer reviews have no impact on purchasing decisions. The sum of coeficient of determination (adjusted R2) is 0.652 or 65.2%, which suggests that the independent variables consisting of product quality, cost, brand image and online customer reviews can contribute an impact of 65.2% to purchasing decisions, whereas the rest (100%-62.2% = 34.8%) is clarified by other variables not included in this study.